(untitled) (Research, Society and Development, 2023)
Acute pancreatitis is an inflammatory process of the pancreas that occurs suddenly. In pancreatitis, digestive enzymes, which should be released into the digestive tract, end up damaging the pancreas itself and other adjacent organs, causing tissue self-digestion. There are many causes of acute pancreatitis. Most cases are secondary to biliary diseases, such as gallstones (including microlithiasis), or excessive alcohol intake (which accounts for 80 to 90% of cases). The main symptom of acute pancreatitis is abdominal pain, and this clinical manifestation is of great variability and can present as a mild and self-limited discomfort to intense, constant and disabling suffering. In typical cases, the pain will be located in the epigastrium and in the periumbilical region, and may radiate to the back, chest, flanks and lower parts of the abdomen (severe, band-like pain radiating to the back). In addition, some cutaneous signs can be observed, such as Grey-Turner’s Sign, Cullen’s Sign, Panniculitis and Fox’s Sign. The diagnosis of acute pancreatitis is defined by the presence of at least two of the three primary characteristics, which are clinical presentation, changes in laboratory tests, and changes in imaging tests. Laboratory tests consist of the analysis of serum amylase and lipase levels. Within a few hours of the onset of symptoms, the levels of these enzymes increase. Increases greater than 3 times the upper limit of normal levels of these enzymes are the recommended ceiling for diagnosis. In addition, imaging tests that may be requested are abdominal ultrasound, computed tomography or magnetic resonance imaging.